Acute stent thrombosis after stent-assisted coiling in an intracranial aneurysm patient carrying two reduced-function CYP2C19 alleles: A case report. Issue 47 (November 2017) - Ding, Lanping; Gu, Zhichun; Wang, Rong; Li, Yichen; Fang, Yun
Abstract: Rationale: Stent thrombosis (ST) remains a thorny issue in spite of dual antiplatelet treatment with aspirin plus clopidogrel after stent-assisted coiling (SAC). We report a first case of acute ST after SAC in an intracranial aneurysm (IA) patient who carries two reduced-function CYP2C19 alleles. Patient concerns: A 43-year-old Chinese male carrying two reduced-function CYP2C19 alleles was treated with a loading dose of clopidogrel 300 mg and aspirin 300 mg before SAC. Unfortunately, life-threatening ST appeared 0.5 h later after SAC. Interventions: A total of 100000U of urokinase was used to dissolve ST. Meanwhile, tirofiban and nodroparin was also administrated to prevent recurrent thrombotic events. Outcomes: A repeated angiography demonstrated a successful reperfusion after thrombolytic treatment. Lessons: The present case demonstrates that CYP2C19 allele carriers may lead to a suppressed antiplatelet effect of clopidogrel and a high risk of ST in the meantime. Therefore, CYP2C19 genetic testing seems to be able to identify patients-at-risk and optimal antiplatelet treatment should be considered in these fragile populations.